Determinan Kemiskinan Di Provinsi Nusa Tenggara Timur - Yanto Kambaru Njuka Tehik; Eva Domu Njurumana (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2015)
Poverty is a multidimensional problem. Poverty shows where a person or group of people can not meet basic their needs and the inability of individuals to interact with the environment to meet social needs. This study is conducted to examine the effect of economic growth (X1), level of population (X2), and the unemployment rate (X3) of the poverty level (Y) and in province of East Nusa Tenggara. The analysis model used in this research is panel data regression with e-viws sofwere version 6. The data used in this research is secondary data in the form of variable economy growth, population and unemployment within five (5) years from 2008 to 2012 on 18 (eighteen) regencies and 1 (one) city East Nusa Tenggara.The conclusions this study showed that the rate of economic growth (X1) has significant negative effect on the level of poverty (y), which means when economic growth decline or reduced, then the level of poverty in the province of East Nusa Tenggara will increase. On the other hand, the level of population (X2) has positive and significant impact on poverty levels (y), which means when the population increases and not followed by employment then level of poverty in the province of East Nusa Tenggara will increase. Meanwhile, the unemployment rate (X3) has positive and significant impact on poverty levels (y) or unemployment affect the increasing levels of poverty in East Nusa Tenggara province.Keywords: Economic Growth (X1), Level of Population (X2), Unemployment Rate (X3), Poverty Level (Y)